Crossbreeding for beef in Ghana and Nigeria - Ngere, L.O. (Editorial Garsi, 1974)
Livestock improvement schemes in Ghana and Nigeria were examined. The ecological zone, livestock production, and efforts towards crossbreeding of West African Dwarf Shorthorn or N'Dama with imported cattle are discussed.